Change in waist circumference with longer time in the US among Hispanic and Chinese immigrants: the modifying role of the neighborhood built environment - Albrecht, Sandra S. (Ann Epidemiol, 2015)
PURPOSE: We examined whether living in neighborhoods supportive of healthier diets and more active lifestyles may buffer immigrants against the unhealthy weight gain that is purported to occur with longer length of US residence. METHODS: Neighborhood data referring to a 1-mile buffer around participants’ baseline home addresses were linked to longitudinal data from 877 Hispanic and 684 Chinese immigrants aged 45-84 years in the Multi-Ethnic Study of Atherosclerosis. We used ethnicity-stratified linear mixed models to examine whether food and activity-based neighborhood measures (healthy food stores, walkability, and recreational facilities) were associated with change in waist circumference (WC) over a 9-year follow-up. RESULTS: Among Hispanics, living in neighborhoods with more resources for healthy food and recreational activity was related to lower baseline WC. However, there was no association with change in WC over time. Among Chinese, living in more walkable neighborhoods was associated with lower baseline WC and with slower increases in WC over time, especially among the most recent immigrant arrivals. CONCLUSIONS: Where immigrants reside may have implications for health patterns that emerge with longer time in the US.